Look and feel for Kwashiorkor - utilizing IMMCU5 - Kamaruzaman, Nor Azam (2019)
Introduction / Background: Malnutrition is an important contributory factor for mortality and morbidity among infant and young children globally and locally with prevalence among Orang Asli (OA) remains high. Pahang which has the highest number of OA population recorded more than two thousand recipients for food basket in 2015 with nearly half were OA. The state had developed a comprehensive manual on assessment and management of malnourished children called The Integrated Management of Malnutrition in Children under 5 (IMMCU5). It emphasizes on detection of severe malnutrition by three simple steps: take weight for age, look for visible severe wasting and feel for oedema of both feet.